2022
DOI: 10.1111/jse.12933
|View full text |Cite
|
Sign up to set email alerts
|

Plant scent and plant–insect interactions—Review and outlook from a macroevolutionary perspective

Abstract: The astonishing diversity of plants and insects and their entangled interactions are cornerstones in terrestrial ecosystems. Co-occurring with species diversity is the diversity of plant secondary metabolites (PSMs). So far, their estimated number is more than 200 000 compounds, which are not directly involved in plant growth and development but play important roles in helping plants handle their environment including the mediation of plant-insect interactions. Here, we use plant volatile organic compounds (VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 168 publications
(217 reference statements)
0
5
0
Order By: Relevance
“…For plant–pollinator relationships an increasing number of studies suggest that similar volatiles attract similar pollinators (Burkle & Runyon, 2019 ; Hetherington‐Rauth & Ramírez, 2016 ; Huang et al, 2015 ; Stökl et al, 2005 ). As with other plant groups, fig volatiles may be phylogenetically constrained (Joffard et al, 2020 ; Schwery et al, 2022 ). The degree to which different levels of phylogenetic distance predicts similarity of chemical cues should correspond to particular pollinator species being more likely to shift within fig sections or subgenera than between them (Cook & Segar, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For plant–pollinator relationships an increasing number of studies suggest that similar volatiles attract similar pollinators (Burkle & Runyon, 2019 ; Hetherington‐Rauth & Ramírez, 2016 ; Huang et al, 2015 ; Stökl et al, 2005 ). As with other plant groups, fig volatiles may be phylogenetically constrained (Joffard et al, 2020 ; Schwery et al, 2022 ). The degree to which different levels of phylogenetic distance predicts similarity of chemical cues should correspond to particular pollinator species being more likely to shift within fig sections or subgenera than between them (Cook & Segar, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For plant-pollinator relationships an increasing number of studies suggest that similar volatiles attract similar pollinators (Burkle & Runyon, 2019;Hetherington-Rauth & Ramírez, 2016;Huang et al, 2015;Stökl et al, 2005). As with other plant groups, fig volatiles may be phylogenetically constrained (Joffard et al, 2020;Schwery et al, 2022). The degree to which different levels of for many herbivorous insect groups (Becerra, 1997;Erbilgin et al, 2014;Murphy & Feeny, 2006;Rigsby et al, 2017).…”
Section: Pegoscapus Tonduzimentioning
confidence: 99%
“…Therefore, macroevolutionary studies, which consider evolutionary history using phylogenetic approaches, offer valuable insights into plant chemicals and plant–insect interactions. Schwery et al (2022) provide a comprehensive review and outlook from the macroevolutionary perspective, focusing on volatile organic compounds (VOCs), the key chemical group mediating plant–insect olfactory communication. It has been suggested that plants produce more than 1700 flower volatiles (Knudsen et al, 2006; Farré‐Armengol et al, 2020), and insects have a relatively large portion of olfactory receptor genes in their genomes that enable them to discriminate numerous and complex olfactory signals (reviewed by Khallaf & Knaden, 2022).…”
Section: The Evolutionary History Of Communicationmentioning
confidence: 99%
“…In this special issue of the Journal of Systematics and Evolution , we present a collection of 10 papers addressing these challenges through original research and comprehensive reviews of relevant subfields. The contributions can be organized into four primary themes: (i) community‐level communication theory (Zu et al, 2022) and its application to plant–pollinator communities (Yang et al, 2022); (ii) the evolutionary history of communication from a phylogenetic and macroevolutionary perspective (Martel et al, 2021; Schwery et al, 2022); (iii) various communication types, including plant–pollinator (Martel et al, 2021), plant–pest (Fang et al, 2023), and plant–fungi–insect interactions (Xu et al, 2023); and (iv) an exploration of different communication factors such as distyly (Zeng et al, 2022), odor dynamics (Feng et al, 2022), chemical structures (Zhang et al, 2022), and the impact of herbicides (Ramos et al, 2022).…”
mentioning
confidence: 99%
“…The hypotheses of phylogenetic constraint versus ecological convergence represent two theoretical extremes; the reality is likely an intermediate dynamic in which both processes shape floral fragrance (Raguso, 2008 ; Schwery et al, 2023 ). While some comparative studies have found phylogenetic structuring of floral scents (Azam et al, 2013 ; Steiner et al, 2011 ), others have found floral scent divergence driven by local biogeographic differences (Moré et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%